Application of Fuzzy Analytic Hierarchy Process (FAHP) for the selection of best student award / Khairu Azlan Abd Aziz ... [et al.] - Abd Aziz, Khairu Azlan; Mohd Idris, Mohd Fazril Izhar; Wan Daud, Wan Suhana; Mohamad Fauzi, Maisarah (UiTM Cawangan Perlis, 2023)
The Best Student Award is an award that students, particularly those who perform best, look forward to receiving. It recognized students who have achieved success in both academic and extra-curricular activities during their undergraduate years. However, there are other challenges in the student selection decision such as having trouble in selecting the student with what characteristic features should be considered and prioritized. Hence, the management needs to take the initiative to make students more satisfied with the new process and result. This study aims to determine the important factors and sub-factors needed to select the student for the best student award and rank them according to the most important influence level. To achieve the objective, the Fuzzy Analytic Hierarchy Process (FAHP) has been used to determine ranking factors including Cumulative Grade Point Average (CGPA), soft skills that students possess, discipline, and participation in extra-curricular activities. Each factor comprises three subfactors. The primary data was collected by distributing questionnaires to six experts, consisting of three (3) academic administrators and three (3) student administrators using Google Forms. Discipline, with a normalized weight of 0.363, is the most important factor in students' selection of excellent students. With a normalized weight of 0.485, the sub-factor teaching and learning process is the most essential for CGPA. With a normalized weight of 0.445, self-confidence is the most important sub-factor under soft skills. Subfactors free from disciplinary action (normalized weight 0.414) are significant for the factor of discipline and committing (normalized weight 0.482) is significant for the factor of extra-curricular activities. Based on this outcome, it shows that Fuzzy AHP is a method that can assist experts to decide under complicated situations and precisely rank all factors and sub-factors. High satisfaction among students with selection decisions will most likely lead to their high and extraordinary fighting spirit.